Mechanical thrombectomy with the Solitaire AB stent for treatment of acute basilar artery occlusion: A single-center experience. (October 2016) - Du, Shiwei; Mao, Gengsheng; Li, Dongmei; Qiu, Ming; Nie, Qingbin; Zhu, Haibo; Yang, Yang; Zhang, Youping; Li, Youxiang; Wu, Zhongxue
Highlights: Twenty-one patients with acute basilar artery occlusion (BAO) were treated with mechanical thrombectomy with the Solitaire AB stent device (Covidien, Irvine, CA, USA). Recanalization was assessed using the Thrombolysis in Cerebral Infarction (TICI) scale system. The mean time from symptom onset to recanalization was 579.00 ± 188.78 min (range: 360–960 min). At 3-month follow-up, eight (38.1%) patients had a good clinical outcome. The Solitaire AB stent device resulted in high recanalization rates without procedural complications and with good clinical outcome. Abstract: Basilar artery occlusion (BAO) remains one of the most devastating subtypes of ischemic stroke, and prognosis is poor if early recanalization is not achieved. The purpose of this study was to evaluate the safety and technical feasibility of mechanical thrombectomy with the Solitaire AB stent (Covidien, Irvine, CA, USA) for the treatment of acute BAO through a single-center experience. Twenty-one patients with acute BAO were treated with mechanical thrombectomy with the Solitaire AB stent device between 1st September 2011 and 1st December 2014. Recanalization was assessed using the Thrombolysis in Cerebral Infarction (TICI) scale system. Clinical outcome was established at discharge by The National Institute of Health Stroke Scale (NIHSS), and the mean time from symptom onset to recanalization determined. Authors had access to identifying information during or after data collection. The clinical status of patients on admission was severe, with a mean NIHSS score of 25.57 ± 5.20 (range: 16–38), and the number of patients with TICI 2b or 3 was 0. The mean time from symptom onset to recanalization was 579.00 ± 188.78 min (range: 360–960 min). At 3-month follow-up, eight (38.1%) patients had a good clinical outcome. At follow-up, the trial of ORG 10172 in acute stroke treatment (TOAST) classification was large-vessel atherosclerosis in 13 patients (61.9%), cardioembolic in seven patients (33.3%), and undetermined in one patient (4.8%). In our series, application of the Solitaire AB stent retriever in acute BAO resulted in a high recanalization rate without procedural complications, and with good clinical outcome. Further prospective trials are needed to confirm the potential clinical benefit of this treatment approach.